Knowledge of HPV and its association with oropharyngeal cancer among dental students: a systematic review and meta-analysis - Albusairi, Khaled; Mandani, Badriyah; Bouresly, Ward; Brahmbhatt, Yash; Alqaderi, Hend; Alhazmi, Hesham (Frontiers in Oral Health, 2025)
BackgroundHuman papillomavirus (HPV) infection is a significant risk factor for oropharyngeal cancer (OPC), yet dental students' knowledge of this association varies widely. Given the critical role dentists play in early detection and prevention, understanding their level of knowledge is essential. This study systematically reviews existing research to assess dental students' awareness of HPV and its link to OPC.MethodsA systematic review and meta-analysis were conducted following PRISMA guidelines. PubMed, ProQuest, and Web of Science databases were searched for studies published up to August 2023. The Newcastle-Ottawa Scale was used to evaluate study quality. A random effects model was applied to calculate pooled prevalence with 95% confidence intervals.ResultsSixteen studies, comprising 6,345 participants, were included. The pooled analysis showed that 69% of dental students had general knowledge of HPV (range: 56%–96.5%; 95% CI: 0.56–0.81), while 77% recognized its association with OPC (range: 18%–96.4%; 95% CI: 0.63–0.89). Significant heterogeneity was observed across studies (Q = 646.34, P < 0.001 for HPV; Q = 804.07, P < 0.001 for HPV-OPC).ConclusionKnowledge gaps among dental students may hinder prevention efforts. Standardized education in dental curricula is crucial to ensure future dentists are well-prepared to address HPV-related conditions and promote early detection in clinical practice.